The impact of teaching by the guided imagination strategy on developing creative expression skills for high school students in Republic of Yemen - Rafiq Allah, Bushra Muhammad Yahya (Journal of Educational and Psychological Sciences, 2023)
The study aimed at identifying the impact of teaching by the guided imagination strategy on developing creative expression skills for high school students in Al-Mahweet Governorate in the Republic of Yemen, in the first semester of the academic year (2021-2022). The study relied on the semi-experimental approach. To achieve the aim of the study, a List of Creative Expression Skills, A Teacher’s Guide for teaching creative expression topics according to the guided imagination strategy, and a Creative Expression Skills Development Test (CESDT) were prepared. The study sample consisted of (106) first-grade high school students, (60) female and (46) male, were selected from two schools in Al-Mahweet Governorate, one for girls and the other for boys, and they were distributed equally into two groups (experimental and control). Among the most important findings of the study: There were statistically significant differences at (0.05) level between the mean scores of students of the experimental and control groups in the CESDT, due to the teaching method variable, and in favor of the experimental group; There were no statistically significant differences at (0.05) level between the mean scores of the experimental group students in the CESDT due to the gender variable; and there were statistically significant differences at (0.05) level between the mean scores of the experimental group students in the pre and post application of the CESDT in favor of the post-test. The study recommended the need to urge teachers to employ the skills of functional expression and creative expression in all educational stages.